Investigating the Role of PES in Reviving the Social and Ecological Fabric of Kodagu. (2016) - Naveen, A. Seema
Abstract: Kodagu is one of the green districts in the Western Ghats, which contributes to a major share of coffee production in India with a rich cultural heritage, a significant part of which is a sustainable outlook in all aspects of life. The district is now witnessing a decline in its cultural and environmental vibrancy due to a number of reasons, notably, rapid urbanization, shift from the natural agricultural systems, destruction of the sacred groves, expansion of coffee plantations and reduction of the native green cover. The negative impact is indicated in various environmental statistical records. The College of Forestry, Ponnampet and University of Agricultural Sciences, Bangalore have proposed the Payment for Ecological Services through landscape labeling that could help alleviate the economic woes of the farmers and consequentially provide an opportunity to restore the ecological balance in Kodagu. The scope of the paper would be to investigate whether PES in conjunction with the cultural and social scenarios would be able to create a cultural renaissance in Kodagu.